2011
DOI: 10.5897/ajb11.828
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glucose, lactate and pyruvate concentrations on in vitro growth of goat granulosa cell

Abstract: Carbohydrates are among the most influential of the numerous components of culture medium that affect metabolism and developmental potential. Glucose, lactate and pyruvate are required for the growth of oocytes and other follicular cells in vitro. The aim of this study was to determine the effects of different concentrations of glucose, lactate and pyruvate on promoting DNA synthesis of granulosa cells in a serum-free medium. Effects of glucose (0.75, 1.5 or 3 mM), pyruvate (0.1 or 0.33 mM) and Llactate (3, 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…[Oocyte di used to det played a ro diameter i contribute Deldar et al, 2011). In this present study, a similar trend of development of glucose was observed.…”
Section: Resultssupporting
confidence: 86%
“…[Oocyte di used to det played a ro diameter i contribute Deldar et al, 2011). In this present study, a similar trend of development of glucose was observed.…”
Section: Resultssupporting
confidence: 86%